SEXUAL ABUSE IN LAURIE HALSE ANDERSON’S NOVEL SPEAK - Dwi Anggriani; M. Amrin Siregar (Universitas Islam Sumatera Utara, 2021)
This paper discusses the impacts of sexual abuse found in the novel Speak which has been selected as the source of data because this novel has a strong impact on sexual abuse victim. The story is about a female teenager who becomes a victim of abuse and it gives her many impacts. The aims of this study are to find out and analyze the impacts of sexual abuse and is conducted based on the concept of sexual abuse, a crime related to sexuality and more specifically related to male and female sexuality. Sexual abuse can include sexual harassment and sexual assault. Sexual abuse is an act that can harm and damage the victims with physical, psychological, sexual and even emotional impacts. This study applies descriptive qualitative method which collects the data taken from the novel that has been read. The result of the study shows that there are three forms of sexual abuse impacts: physical, psychological and behavioral.